2015
DOI: 10.1002/cncr.29564
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Notch pathway: A potential therapeutic approach for desmoid tumors

Abstract: BACKGROUNDDesmoid tumors (DTs) are rare mesenchymal lesions that can recur repeatedly. When it is feasible, DTs are surgically resected; however, this often results in high recurrence rates. Recently, treatment with PF‐03084014, a potent γ‐secretase inhibitor, has been shown to have antitumor activity in several tumor types by affecting the WNT/β‐catenin pathway. Consequently, Notch pathway inhibition by PF‐03084014 might be a promising approach for DT treatment.METHODSThe expression of Notch pathway component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 38 publications
(96 reference statements)
2
56
0
1
Order By: Relevance
“…Exposure of resistant OS cells to 6 µM CDDP resulted in cell cycle arrest at the G0/G1‐phase in agreement with other scholars studies . We also found that DAPT promoted G0/G1‐phase arrest via reduction of Cyclin D1, Cyclin E1, CDK2, SKP2, c‐Myc and increase p21, which were consistent with the findings of other earlier studies showed that DAPT induces G0/G1‐phase arrest in human OS cells and other tumors . It is not surprising that the G0/G1‐phase arrest induced by CDDP and DAPT combination treatment was significantly greater than monotherapy group.…”
Section: Discussionsupporting
confidence: 92%
“…Exposure of resistant OS cells to 6 µM CDDP resulted in cell cycle arrest at the G0/G1‐phase in agreement with other scholars studies . We also found that DAPT promoted G0/G1‐phase arrest via reduction of Cyclin D1, Cyclin E1, CDK2, SKP2, c‐Myc and increase p21, which were consistent with the findings of other earlier studies showed that DAPT induces G0/G1‐phase arrest in human OS cells and other tumors . It is not surprising that the G0/G1‐phase arrest induced by CDDP and DAPT combination treatment was significantly greater than monotherapy group.…”
Section: Discussionsupporting
confidence: 92%
“…Although Wnt signaling mainly plays a role in the maintenance of adult stem cells, recent studies have explored the integral role of Wnt signaling in cancer stem-like cells [19, 20]. However, in specific environments, Notch, which was identified to be mutually regulated by Wnt, participates in the stemness and differentiation [34]. For example, Notch signaling is likely to inhibit specific differentiation lineages and to maintain the sustainability of self-renewal tumor populations in intestinal epithelial cells, hematopoietic stem cells and esophageal adenocarcinoma cells, and these features are characteristics of stemness [3537].…”
Section: Discussionmentioning
confidence: 99%
“…Так, в своей работе H. Shang и со-авт. [39] сообщают об обнаружении нового сигнального пути, обусловливающего неконтролируемую пролифера-цию фибробластов -сигнальный путь NOTCH, который представляется потенциально важным и обнадеживаю-щим в плане поиска новых терапевтических агентов. Ле-чебный эффект может быть основан на ингибировании гамма-секретазы, которая в свою очередь блокирует сиг-нальный путь NOTCH, оказывая противоопухолевое воз-действие.…”
Section: Discussionunclassified